Charitable Behaviour and the Big Five Personality Traits: Evidence from UK Panel Data - Sarah Brown; Karl Taylor (Institute for the Study of Labor (IZA), 2015)
This paper investigates the association between personality traits and charitable behaviour, namely donations of time and money, using data from Understanding Society, the most recent large scale UK household longitudinal survey. Due to the censored nature of the outcome variables, i.e. some individuals do not engage in charitable behaviour, we employ censored quantile regression models. Personality traits are classified according to the 'Big Five' taxonomy: openness to experience; conscientiousness; extraversion; agreeableness; and neuroticism. The quantile approach allows us to explore the effect of personality traits across the entire distribution of charitable behaviour rather than just at the mean, which has generally been the case in the existing literature. In general, after conditioning on an extensive set of controls, conscientiousness and neuroticism are found to be inversely related to donating time and money, whilst openness to experience, which has a positive effect, is the dominant trait in terms of magnitude. Interestingly, personality traits are found to have a stronger association with donations of time and money at the extreme points of the distribution of donations relative to that at the median, thereby highlighting the additional information revealed by quantile approach.
Keywords: C24; D03; H41; N3; 330; censored quantile regression; charitable donations; personality traits; volunteering